Across the spectrum : understanding issues in evangelical theology - Boyd, Gregory A., 1957-; Eddy, Paul Rhodes (Grand Rapids Baker Academic, 2020)
"This accessible yet comprehensive primer helps readers understand the breadth of viewpoints on major issues in evangelical theology. Now updated and revised throughout"--
Includes bibliographical references and index.
Keywords: Evangelicalism; Theology, Doctrinal